Rhododendrons: A major resource of fuelwood in high altitude region of Arunachal Himalaya, India - Ashish Paul; PIJUSH KUMAR DUTTA; MOHAMED LATIF KHAN; ASHESH KUMAR DAS (Society for Indonesian Biodiversity, 2019)
Abstract. Paul A, Dutta PK, Khan ML, Das AK. 2019. Rhododendrons: A major resource of fuelwood in high altitude region of Arunachal Himalaya, India. Biodiversitas 20: 2628-2635. This study highlights rhododendrons consumption for fuelwood in Tawang district of Arunachal Pradesh. Rhododendron spp. contributed the highest (60% and 58%), Quercus spp. (33% and 40%) while Alnus species (7% and 2%) of the total fuelwood consumption in villages between 1800-2100 m and 2100-2400 m altitude, respectively. Consumption was recorded highest (3.45 kg/capita/day) in villages between 2100-2400 m than 1800-2100 m altitude (3.24 kg/capita/day). Fuelwood consumption was not significantly varied with altitudes (U = 364, p = 0.864). However, it was significantly different among species at altitude 1800-2100 m (F = 6.205, p < 0.05) and 2100-2400 m (?2 = 31.319, p < 0.001). Irrespective of altitude, consumption was significantly different among the species (?2 = 41.289, p < 0.001). Rhododendron arboreum and Rhododendron thomsonii with a mean rank of 47.35 and 49.88, respectively, were the most used fuelwood, followed by Quercus griffithii (33.08), Quercus sp. (26.04) and Alnus sp. (8.65). The remote villages, mostly use fuelwood for boiling, cooking and space heating. Intensive consumption pressure will lead to habitat degradation and mount fuelwood crisis in coming years. The present pilot study could be a basis to develop suitable conservation and management of energy resources, particularly the rhododendrons.